2015
DOI: 10.1142/s2301385015500041
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Genetic Algorithm System for Multi-UAV Surveillance: Algorithm and Flight Testing

Abstract: This paper discusses the development and testing of a flexible genetic algorithm (GA)-based system used for tasking a team of unmanned aerial vehicles (UAVs) to complete a coordinated surveillance mission. The GA development, laboratory testing of the GA to ensure convergence to a \good" solution, integration testing with two ground stations, and the field testing of the algorithms are explained. The algorithm was found to be robust and flexible enough to work in various settings with different UAV types and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The complexity of the models used in agent-based approaches offer no assurance of an optimal final result and thus are often avoided [17]. GA are well known optimizer that have been shown to successfully plan balanced missions for simultaneous mutli-UAV sets [18] surveying multiple POIs [2] and are particularly well-suited in UAV tasking and path planning [18][19][20][21][22]. Several GA approaches for coordinated tasking in surveillance missions under number of targets, task load requirements and reconnaissance time constraints exist in literature [23][24][25][26].…”
Section: Multiple Aircraft Path Planning Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The complexity of the models used in agent-based approaches offer no assurance of an optimal final result and thus are often avoided [17]. GA are well known optimizer that have been shown to successfully plan balanced missions for simultaneous mutli-UAV sets [18] surveying multiple POIs [2] and are particularly well-suited in UAV tasking and path planning [18][19][20][21][22]. Several GA approaches for coordinated tasking in surveillance missions under number of targets, task load requirements and reconnaissance time constraints exist in literature [23][24][25][26].…”
Section: Multiple Aircraft Path Planning Literaturementioning
confidence: 99%
“…A flight tested GA method using homogeneous fixed wing UAVs was investigated et al [2] where the fitness function balanced UAV flight times, example shown in Fig. 1, was able to converge on a desktop PC in less than 5 min.…”
Section: Multiple Aircraft Path Planning Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, with the advances of dynamics [1,2], navigation [3,4], and sensors [5,6], more civilian applications have been realized for UAVs, such as surveillance [7,8], aerial photography [9,10], search and rescue [11,12], and others. For all of these applications with multiple UAVs, one critical technical problem is that the UAVs may collide with each other in the increasingly dense airspace.…”
Section: Introductionmentioning
confidence: 99%